Exploring Technostress in Accounting Perspectives in the Era of Digital Transformation: A Systematic Literature Review - Sulhia, Baiq Aulia (Postgraduate, University of Mataram, 2026)
This study aims to gain a comprehensive understanding of the study related to the relationship between technostress and the use of digital technology in an accounting perspective. The Systematic Literature Review (SLR) approach with the PRISMA framework is used to minimize bias over diverse previous research. Software Publish or Perish as a tool and Google Scholars as a search engine. 25 relevant scientific articles were obtained in accordance with the inclusion and exclusion criteria in the period 2015-2025. The results of this study show that scientific articles related to the influence of technostress on the use of digital technology in accounting perspectives have diverse and varied results. It is known that there are 5 technostress indicators that are often used by previous research in measuring the level of technostress of its users. This research is expected to be able to contribute to mapping related to research conducted on technostress in the use of digital technology in an accounting perspective.